Lithium-air battery
Patent Information
- Application Number
- JP2023577695
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-09-27
- Filing Date
- 2022-06-16
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-06-16
AI Technical Summary
Lithium-air batteries face performance limitations due to the slow rate of electron transfer and restricted oxygen flow caused by the accumulation of lithium oxide and other by-products at the cathode, which reduces the influx of oxygen and affects battery efficiency and lifespan.
The lithium-air battery design includes a cathode with an array of carbonaceous structures featuring interconnected pores and pathways to facilitate oxygen diffusion, storage cavities for by-products, and a hydrophobic/hydrophilic surface treatment to manage water droplets, enhancing oxygen availability and preventing flooding.
This design improves the efficiency and lifespan of lithium-air batteries by maintaining oxygen supply and preventing water-induced flooding, thereby increasing specific energy capacity and discharge performance.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This patent application is a continuation-in-part of and claims priority to U.S. Patent Application No. 17 / 485,888, entitled "LITHIUM-AIR BATTERY," filed September 27, 2021, which claims priority to U.S. Provisional Patent Application No. 63 / 211,445, entitled "LITHIUM-AIR BATTERY," filed June 16, 2021, all of which are assigned to the assignee of the present application. The disclosures of the prior applications are incorporated herein by reference in their entireties in this patent application.
[0002] Technical Field The present disclosure relates generally to lithium-air batteries, and more particularly to lithium-air batteries having cathodes with pore pathways. [Background technology]
[0003] Lithium-air batteries can be used to power a wide variety of loads, from portable communication devices to electric vehicles. Lithium-air batteries use oxygen as the cathode active material, for example, to oxidize lithium at the anode during the battery discharge cycle and reduce oxygen to lithium oxide at the cathode during the battery discharge cycle. The reverse occurs during the battery charge cycle. By using oxygen supplied from the ambient air as the cathode active material, lithium-air batteries do not need to store the cathode active material. Although lithium-air batteries have a very high theoretical specific energy (e.g., over 11,000 Wh / kg), the actual specific energy may be lower due to slow electron transfer rates and / or incomplete utilization of the cathode porous geometry for the redox reaction, and the accumulation of lithium oxide and other by-products at the cathode during the operation cycle of the lithium-air battery may limit the flow of oxygen to and across the cathode, thereby degrading the performance of the lithium-air battery. Therefore, further improvements in lithium-air batteries are desirable. Summary of the Invention
[0004] This summary is provided to introduce in a simplified form some of the concepts that are further described below in the detailed description. This summary is not intended to identify key features or essential features of the claimed subject matter, nor is it intended to limit the scope of the claimed subject matter.
[0005] One innovative aspect of the subject matter described in this disclosure may be implemented in a lithium-air battery. The lithium-air battery may include an anode, a cathode disposed opposite the anode, an electrolyte dispersed throughout the cathode, and one or more openings configured to selectively expose the cathode to ambient air. In some implementations, the cathode may be formed from an array of carbonaceous structures and may include a plurality of pores defined by a first group of the carbonaceous structures, a plurality of interconnected pathways defined by a second group of the carbonaceous structures, and one or more cavities formed within or associated with each of the pathways. In some examples, the pores may be configured to allow oxygen provided from ambient air to enter the cathode, the interconnected pathways may be configured to diffuse oxygen throughout the cathode, and each of the cavities may be configured to store lithium metal. In some embodiments, the anode is comprised of lithium metal.
[0006] In various embodiments, each of the carbonaceous structures may be based on the coalescence of a corresponding group of carbon nano-onion (CNO) particles. In some examples, each of the carbonaceous structures may include a plurality of interconnected graphene flakes. In other examples, each of the carbonaceous structures may include one or more of flat graphene, wrinkled graphene, curved graphene, or porous non-hollow spherical particles. In some embodiments, the CNO particles have a radius between about 5 nanometers and 500 nanometers. In other embodiments, at least a portion of the CNO particles of the first group of carbonaceous structures have a radius of more than 100 nanometers and include a plurality of cavities. In some other examples, each of the carbonaceous structures includes a three-dimensional (3D) stack of graphene nanosheets.
[0007] In some implementations, at least a portion of the CNO particles of the first group of carbonaceous structures may be configured to be hydrophobic. In some examples, the hydrophobic CNO particles of the first group of carbonaceous structures inhibit the movement of water droplets along the surface toward one or more of the plurality of pores. In other implementations, at least a portion of the CNO particles of the second group of carbonaceous structures may be configured to be hydrophilic. In some examples, the hydrophilic CNO particles of the second group of carbonaceous structures allow water droplets to form a continuous water film along the surface of each of the hydrophilic CNO particles. In some aspects, the continuous water film may be in equilibrium due to cohesive forces within the continuous water film and adhesive forces between the continuous water film and the surface of each of the hydrophilic CNO particles. Surface tension forces associated with the continuous water film prevent water droplets of the continuous water film from accumulating on the cathode.
[0008] In some examples, the lithium-air battery may also include a plurality of other interconnected pathways defined by a third group of carbonaceous structures. In some examples, the plurality of other interconnected pathways may be configured to remove undesired by-products from at least a portion of the interconnected pathways defined by the second group of carbonaceous structures. In other examples, the lithium-air battery may include a separator disposed between the anode and the cathode.
[0009] In some other implementations, the lithium-air battery may also include a protective layer disposed on the anode. In some examples, the protective layer may include a polymer network deposited on one or more exposed surfaces of the anode, the polymer network including a carbonaceous structure grafted with a plurality of fluorinated polymer chains crosslinked to each other, and a lithium fluoride (LiF) membrane formed from the polymer network and the lithium provided by the anode. In some embodiments, the lithium-air battery may also include an outer layer deposited on the lithium fluoride membrane. The outer layer may include one or more of a polymer or an epoxy encapsulated ionic conductor.
[0010] The details of one or more embodiments of the subject matter described in this disclosure are set forth in the accompanying drawings and the description below. Other features, aspects, and advantages will become apparent from the description, drawings, and claims. It should be noted that the relative dimensions of the following figures may not be drawn to scale.
[0011] The drawings described below are for illustration purposes only and are not intended to limit the scope of the present disclosure. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 shows a diagram illustrating an exemplary battery, according to some embodiments. [Diagram 2] FIG. 2 shows a diagram illustrating the cathode of the battery of FIG. 1 according to some embodiments. [Diagram 3] 1 shows a diagram of a polymer network, according to some embodiments. [Figure 4] 1A and 1B show micrographs of various carbonaceous materials according to some embodiments. [Figure 5A] 1 shows an SEM micrograph of graphene powder, according to some embodiments. [Figure 5B]1 shows an SEM micrograph of nodular carbon produced by a thermal process, according to some embodiments. [Figure 5C] 1 shows an SEM micrograph of carbon dioxide (CO2) treated carbon, according to some embodiments. [Figure 5D] 1 shows an SEM micrograph of carbon dioxide (CO2) treated carbon, according to some embodiments. [Figure 6] 1 shows a micrograph of three-dimensional (3D) graphene after carbon dioxide (CO2) treatment, according to some embodiments. [Figure 7] 1 shows a graph illustrating an exemplary distribution of pore volume versus pore width for an exemplary carbonaceous particle, according to some embodiments. [Figure 8A] An example illustrating the hydrophobic behavior of few-layer graphene (FLG), which has 3 to 15 layers of carbon atoms, is shown. [Figure 8B] 1 shows an example illustrating an exemplary flooding of a lithium-air battery. [Figure 9A] 1 shows an example illustrating the state of charge of a lithium-air battery. [Figure 9B] 1 shows an example illustrating the discharge state of a lithium-air battery. [Figure 10] 1 shows examples illustrating various types of FLGs. [Figure 11] 11 shows an example 1100 illustrating an agglomerate formed from a number of single particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Like reference numbers and designations in the various drawings indicate like elements.
[0014] The following description is directed to several exemplary embodiments for the purpose of illustrating the innovative aspects of the present disclosure. However, those skilled in the art will readily recognize that the teachings herein can be applied in many different ways. The described embodiments can be implemented in any type of electrochemical cell, battery, or battery pack, and can be used to compensate for various performance-related defects. Thus, the disclosed embodiments should not be limited by the examples provided herein, but rather encompass all embodiments contemplated by the appended claims. Furthermore, well-known elements of the present disclosure will not be described in detail or will be omitted so as not to obscure the relevant details of the present disclosure.
[0015] As used herein, "porosity" refers to the ratio of the volume of pores or voids in a material to the geometric volume of the material. Porosity can be measured using suitable methods, such as, but not limited to, BET and gas permeability measurements. As used herein, the terms "about" and "approximately" are used to provide a margin, such as to indicate that a given value at the endpoint of a numerical range may be "a little above" or "a little below" the endpoint. The degree of margin for a particular variable can be readily determined by one of ordinary skill in the art based on the context. When used herein with respect to an identified characteristic or situation, "substantially" means a degree of deviation small enough so as not to measurably impair the identified characteristic or situation. The exact degree of acceptable deviation may depend on the particular context in some instances.
[0016] Furthermore, numerical data such as concentrations, amounts, etc. may be presented in the form of a range herein. It should be understood that such range formats are used merely for convenience and brevity, and should be interpreted flexibly to include not only the numerical values explicitly recited as range limitations, but also all individual numerical values or subranges subsumed within the range, as if each numerical value and subrange were explicitly recited. For example, a numerical range of about 1 to about 2.5 should be interpreted not only to include the explicitly recited limitations of 1 to about 2.5, but also to include individual numerical values such as 2, 3, 4, and subranges such as 1 to 3, 2 to 4, etc. The same principle also applies to ranges reciting only one numerical value, such as "less than about 2.5," which should be interpreted to include all of the values and ranges recited above. Moreover, such interpretation should be applied regardless of the breadth of the range or characteristic being described.
[0017] Batteries typically include several electrochemical cells that can be connected in series and / or parallel networks to power a wide variety of devices, such as (but not limited to) mobile phones, laptop computers, electric vehicles (EVs), factories, and buildings. Electrolytes are a key component in electrochemical cells and batteries of all kinds, especially lithium-based batteries, whose performance can be limited by the type of electrolyte used or by uncontrolled battery side reactions. As a result, optimizing the electrolyte can improve the overall performance, including cyclability, specific discharge capacity, discharge capacity retention, safety, and lifespan of the respective batteries.
[0018] Lithium-air batteries use oxygen supplied from the ambient air as the cathode active material and lithium metal as the anode. The use of a porous cathode in a lithium-air battery allows the gaseous oxygen supplied from the ambient air to diffuse throughout the cathode to react with lithium ions during the battery's discharge reaction, and allows the gaseous oxygen to return to the ambient air during the battery's charging process. By using oxygen as the cathode active material, lithium-air batteries can provide greater energy storage capacity than other types of batteries, either primary or rechargeable, due to the abundance of oxygen available at the cathode. In other words, by using oxygen as the cathode active material, lithium-air batteries do not need to store cathode active material, so the specific energy and energy storage capacity of the lithium-air battery are not limited by the amount of cathode active material that can be stored in the cathode.
[0019] As the lithium-air battery cycles, oxygen reduction can occur at the three-phase boundary where the solid (cathode), liquid (electrolyte) and gas (oxygen) come into contact with each other. In the alternative, such a configuration provides available pathways for lithium ions to move and / or be transported in the liquid electrolyte, available pathways for gaseous oxygen to move and / or be transported in pore pathways in the cathode, and available pathways for electrons to be conducted in the carbonaceous material in the cathode. Thus, highly porous cathode structures can be used in lithium-air batteries to increase the available electrochemical reaction area and thereby increase current conduction from the lithium-air battery.
[0020] During successive discharge and charge cycles of a lithium-air battery, discharge products generated at the cathode can kinetically affect the battery performance and reduce the specific energy, energy capacity, and lifespan of the battery. For example, chemical reactions of lithium ions with oxygen at the cathode can produce lithium dioxide (Li2O) and lithium superoxide (Li2O2). Lithium dioxide, and in some instances lithium superoxide, are insoluble in certain types of electrolytes used in lithium-air batteries and therefore cannot diffuse away from the cathode through the electrolyte. Instead, these lithium oxide products can become trapped within the cathode and accumulate in various pores, particularly at the pore entrances (e.g., pore "mouths") and pathways responsible for supplying oxygen from the ambient air into the cathode during the battery's operating cycle. Unchecked accumulation of such by-products can clog or block these pores and / or pathways, thereby reducing the amount of oxygen available at the cathode to participate in the chemical reactions associated with the generation of electric current in the lithium-air battery.
[0021] Aspects of the present disclosure recognize that conventional lithium-air batteries may not be able to remove lithium oxide products from the cathode and therefore may not be able to control the accumulation of these lithium oxide products within the pores and / or channels of the cathode. According to various aspects of the subject matter disclosed herein, an interconnected network of storage channels and storage cavities of various dimensions may be provided within the cathode of the lithium-air battery to extract or remove the accumulation of these products from the pores and / or channels responsible for drawing oxygen from the ambient air to the cathode, thereby increasing the amount of oxygen these pores and / or channels can deliver to the cathode during the charge and discharge cycles of the lithium-air battery. By increasing the amount of oxygen available at the cathode to react with lithium oxide and lithium ions, respectively, during the charge and discharge cycles of the battery, aspects of the subject matter disclosed herein may increase the specific energy capacity and effective life of the lithium-air battery. In some instances, these pathways may be defined in shape, size, and orientation by porous, non-hollow, carbonaceous spherical particles that coalesce with one another to form larger porous carbonaceous structures within the cathode.
[0022] FIG. 1 shows a diagram illustrating an exemplary battery 100, according to some embodiments. The battery 100 can be a lithium-air battery in fluid communication with ambient air 170 associated with an environment external to the battery 100. In some embodiments, the battery 100 has a body 105 that can include a cathode 110, an anode 120 disposed opposite the cathode 110, an electrolyte 130, a solid electrolyte interphase interface (SEI) layer 140, a polymer network 150, and a barrier layer 160. In some other embodiments, one or more of the SEI layer 140 or the polymer network 150 can be omitted from the battery 100. Although not shown in FIG. 1 for simplicity, the battery 100 can include a first substrate disposed adjacent to the cathode 110, on which the cathode 110 can be disposed, and can further include a second substrate disposed adjacent to the anode 120, on which the anode 120 can be disposed. In some embodiments, the first and second substrates may be solid copper metal foils that can be selectively etched, coated with carbonaceous materials, and / or treated with materials suitable for varying or tuning the energy capacity and specific energy of battery 100. In other embodiments, the first and second substrates may include or be formed from a selection of aluminum, copper, nickel, titanium, stainless steel, and / or one or more carbonaceous materials.
[0023] In some other embodiments, the first and second substrates may be at least partially foam-based, selected from any one or more of metal foam, metal web, metal screen, perforated metal, or sheet-based 3D structures. In some aspects, the first and second substrates may be metal fiber mats, metal nanowire mats, conductive polymer nanofiber mats, conductive polymer foams, conductive polymer coated fiber foams, carbon foams, graphite foams, or carbon aerogels. In some other aspects, the first and second substrates may be carbon xerogels, graphene foams, graphene oxide foams, reduced graphene oxide foams, carbon fiber foams, graphite fiber foams, exfoliated graphite foams, or any combination thereof. The particular composition and configuration of the first and second substrates may vary depending on the particular end use application and / or performance requirements of the battery 100.
[0024] The cathode 110 may function as a positive electrode of the battery 100. In some embodiments, the cathode 110 may include a plurality of interconnected pores 112 and pathways 114 that allow oxygen supplied from the ambient air 170 to diffuse or permeate throughout the cathode 110 during the operating cycle of the battery 100. The pores 112 and pathways 114 may be defined by various porous non-hollow carbonaceous spherical particles disposed, distributed, or otherwise arranged throughout one or more portions of the cathode 110. Groups of porous non-hollow carbonaceous spherical particles may coalesce with one another to form larger carbonaceous structures within the cathode 110 (for simplicity, neither the porous non-hollow carbonaceous spherical particles nor the larger carbonaceous structures are shown in FIG. 1). The porous non-hollow carbonaceous spherical (NHCS) particles may join with one another at various concentration levels to form larger carbonaceous structures, and higher concentration levels may be associated with higher electrical conductivity. In various embodiments, the first group of pores 112 and channels 114 may be arranged and sized to allow oxygen supplied from the ambient air 170 to enter and diffuse throughout the cathode 110, and the second group of channels 114 and cavities 116 may be arranged and sized to remove undesirable chemical by-products 180 from the first group of pores 112 and channels 114. In some examples, the second group of channels 114 and cavities 116 may hold or store the by-products 180 removed from the first group of pores 112 and channels 114. In this manner, the second group of channels 114 and cavities 116 may direct the by-products 180 away from the first group of pores 112 and channels 114 that may accumulate within the cathode 110 and / or adhere to the surfaces of the first group of pores 112 and channels 114. As used herein, the terms "transport pores" and "transport pathways" may refer to a first group of pores 112 and pathways 114, and the terms "storage pathways" and "storage cavities" may refer to a second group of pathways 114 and cavities 116, as described in more detail with respect to FIG. 2.
[0025] In various embodiments, cathode 110 may include one or more metal catalysts that can improve the reaction rate of the oxygen reduction process in battery 100, for example to increase the specific capacity of battery 100. For example, in some embodiments, manganese, cobalt, ruthenium, platinum, silver, or mixtures of cobalt and manganese, either in pure metallic form or as compounds formed with additional metals or other elements, may be used as catalysts for cathode 110. In some examples, the use of a manganese oxide catalyst in cathode 110 may result in a specific capacity of about 3,137 mA·H / g of carbon.
[0026] Anode 120 may function as the negative electrode of battery 100. In some embodiments, anode 120 may be formed as a single layer of lithium metal (e.g., elemental lithium) without any carbon or carbonaceous materials. That is, unlike the anodes used in many conventional lithium-air batteries, anode 120 of battery 100 does not include a carbon scaffold or other carbonaceous materials, but instead includes lithium metal. As a result, anode 120 may provide more lithium for oxidation than a similarly sized carbon-based anode, thereby increasing the energy capacity and specific energy of battery 100 compared to such conventional lithium-air batteries. In some examples, anode 120 may function with a solid electrolyte configured to inhibit the formation and growth of lithium dendrites from anode 120.
[0027] The electrolyte 130 may be dispersed throughout the cathode 110 or in contact with one or more surfaces of the anode 120. The electrolyte 130 may be any suitable material or mixture capable of transporting lithium ions between the anode 120 and the cathode 110 during an operating cycle of the battery 100. In some implementations, the electrolyte 130 may be a liquid phase electrolyte (e.g., an aprotic liquid phase electrolyte solution). In other implementations, the electrolyte 130 may be a solid polymer, a gel polymer (such as an inorganic glassy or ceramic electrolyte), among other examples. In some examples, the electrolyte 130 may begin in a gel phase and then solidify after activation of the battery 100.
[0028] The SEI layer 140 may be disposed on one or more surfaces of the anode 120, in proximity to or in contact with the electrolyte 130. In some examples, the SEI layer 140 may be formed on the anode 120 in response to a reaction between lithium provided by the anode 120 and the electrolyte 130 during an operating cycle of the battery 100. The SEI layer 140 may include tin, manganese, molybdenum, and / or fluorine compounds. The cations provided by the molybdenum interact with the anions provided by the fluorine compounds to form tin(II) fluoride (SnF2), manganese(II) fluoride (MnF2), silicon nitride (Si3N4), lithium nitride (Li3N), lithium nitrate (LiNO3), lithium phosphate (Li3PO4), manganese oxide, or lithium lanthanum zirconium oxide (LLZO, Li7La3Zr2O4). 12 ), one or more types or structures of salts may be produced, such as, but not limited to:
[0029] In some implementations, the SEI layer 140 may include a mechanical strength enhancer (not shown for simplicity) that provides structural support for the battery 100. In some examples, the mechanical strength enhancer may prevent lithium dendrites from forming on and / or growing from the anode 120. The mechanical strength enhancer may be formed as a protective coating on the anode 120 and may include one or more of carbon allotropes, carbon nano-onions (CNO), nanotubes (CNT), reduced graphene oxide, graphene oxide (GO), and / or carbon nanodiamonds. In other implementations, the SEI layer 140 may not include any mechanical strength enhancer.
[0030] The polymer network 150 may be deposited or formed on one or more exposed surfaces of the anode 120. In some implementations, the polymer network 150 may be evenly interspersed across one or more portions of the SEI layer 140 and may include various carbonaceous structures grafted with fluorinated polymer chains crosslinked to one another (for simplicity, neither the carbonaceous structures nor the fluorinated polymer chains are shown in FIG. 1 ). Specifically, a carbonaceous material may be grafted with fluorinated polymer chains and deposited on one or more exposed surfaces of the anode 120. The fluorinated polymer chains may be crosslinked to form the polymer network 150 upon complexing with lithium metal from the anode 120 via a Wurtz reaction. When formed in this manner, the polymer network 150 may inhibit the formation of lithium dendrites from the anode 120. In some implementations, the carbonaceous material forming at least a portion of the polymer network 150 may include (but is not limited to) graphene, few layer graphene, multilayer graphene, graphene nanoparticles, 3D graphene scaffolds, and the like. The carbonaceous material may be chemically grafted with fluorinated polymer chains via carbon-fluorine (CF) bonds. In some embodiments, these CF bonds may chemically react with lithium metal from the anode 220 to generate highly ionic carbon-lithium bonds (C-Li). The C-Li bonds may react with the CF bonds between the carbonaceous material and the fluorinated polymer chains to form new carbon-carbon bonds. These new carbon-carbon bonds may also be used to crosslink the polymer chains to form the polymer network 150.
[0031] In some implementations, the polymer network 150 may include a layer of lithium fluoride (not shown for simplicity). The lithium fluoride layer may be formed in response to chemical bonding between the lithium ions 122 and fluorine ions. In some aspects, the lithium fluoride layer may also include lithium fluoride created by the "novel" carbon-carbon bonds described above. In some examples, the lithium fluoride layer may be uniformly distributed along the periphery of the polymer network 150 such that the lithium ions 122 are less likely to bond and / or react with each other and more likely to bond and / or react with the fluorine atoms available through the fluorinated polymer chains embedded in the polymer network 150. In other implementations, the battery 100 may not include a polymer network 150.
[0032] The barrier layer 160 may be removably disposed on an exterior surface of the battery body 105 adjacent the cathode 110. When the battery 100 is at rest (e.g., in a warehouse or on a shelf prior to purchase and activation by a user), the barrier layer 160 may be attached to the battery body 105 and arranged such that the pores 112 and channels 114 associated with the cathode 110 are sealed to the ambient air 170. In this manner, the barrier layer 160 may prevent oxygen provided from the ambient air 170 from entering the cathode 110 and reacting with the lithium in the battery 100. In this manner, the barrier layer 160 may prevent inadvertent activation of the battery 100 while at rest (e.g., in a warehouse or on a shelf prior to purchase and activation by a user).
[0033] In some implementations, a user may activate the battery 100 by removing the barrier layer 160 from the exterior surface of the battery body 105. For example, if the barrier layer 160 is removed or is not present for some other reason, oxygen supplied from the ambient air 170 may enter the pores 112 and channels 114 formed in the cathode 110 and diffuse throughout the cathode 110. As previously mentioned, oxygen may be used to oxidize lithium supplied from the anode 120 during the battery discharge cycle and may be used for oxygen reduction reactions during the battery discharge cycle. Thus, by removing the barrier layer 160 from the exterior surface of the battery body 105, the battery 100 is activated so that oxygen supplied from the ambient air 170 may enter the cathode 110 and participate in various chemical reactions within the battery 100.
[0034] In some embodiments, the battery 100 may include a separator (not shown for simplicity) that may further inhibit dendrite formation on and growth from the anode 120. The separator may have similar ionic conductivity as the electrolyte 130 and still inhibit lithium dendrite formation. In some embodiments, the separator may be formed from a ceramic-containing material that does not chemically react with metallic lithium, and may thus be used to control lithium ion transport through the separator while preventing short circuits by impeding the flow or passage of electrons through the electrolyte 130.
[0035] As previously mentioned, when the battery 100 is configured to operate as a lithium-air battery, oxygen supplied from the ambient air 170 is used as the active cathode material. The use of oxygen supplied from the ambient air 170 may ensure a sufficient supply of active material to operate the lithium-air battery 100 without storing any active material in the cathode 110. Specifically, during a battery discharge cycle, lithium supplied from the anode 120 is oxidized by the ambient air 170 to produce lithium ions 122 and free electrons 124. The half-reaction occurring at the anode 120 may be expressed as follows: Li⇔Li + +e - (Formula 1)
[0036] Lithium ions 124 migrate from the anode 120 to the cathode 110 through the electrolyte 130. Oxygen gas (O2) supplied from the ambient air 170 enters the transport pores 112 of the cathode 110 and diffuses throughout the cathode 110 through the transport pathways 114. The oxygen gas reacts with the lithium ions 122 at the cathode 110 to produce lithium oxide. Free electrons 124 can migrate from the anode 120 to the cathode 110 via an external circuit, thereby providing a current that can power a load 190 coupled to the external circuit. The half-reaction occurring at the cathode 110 can be expressed as follows: 4Li+O2→2Li2O(E 0 =2.9V) (Formula 2) 2Li+O2→Li2O2(E 0 =3.1V) (Formula 3)
[0037] During each battery charging cycle, the above process is reversed: oxygen supplied from the ambient air 170 donates electrons to at least a portion of the lithium oxide in the cathode 110 to produce lithium ions 122 and electrons 124. The electrochemical potential between the anode 120 and the cathode 110 can transport these lithium ions 122 from the cathode 110 through the electrolyte 130 back to the anode 120. The lithium ions 122 can accumulate in the anode 120 and plate lithium onto the anode 120, thereby replenishing the lithium supply in the anode 120.
[0038] As previously mentioned, the chemical reaction of the lithium ions 122 with oxygen at the cathode 110 produces lithium oxides (such as lithium peroxide (Li2O2) and lithium superoxide (Li2O)) as unwanted by-products. Lithium oxides are insoluble in aprotic electrolytes and therefore cannot be dispersed from the cathode 110 via the electrolyte 130. Instead, these undesirable by-products may become trapped within the cathode 110 and attach to the transport pores 112 and transport pathways 114 within the cathode 110 after each discharge cycle of the battery 100. Over time, these by-products may accumulate on and / or in the various transport pores 112 and transport pathways 114 involved in diffusing oxygen from the ambient air 170 throughout the cathode 110, which may clog or block the various transport pores 112 and transport pathways 114, thus reducing the amount of oxygen available to react with lithium provided by the anode 120. The resulting decrease in the amount of available oxygen may reduce the amount of lithium ions 122 and free electrons 124 produced during an operating cycle of the battery 100, and therefore may reduce the amount of current that can be delivered to the load 190.
[0039] In some aspects, the production of these by-products can be expressed as follows: Li + +e - +O2+ * →LiO2 (Formula 4) Li + +e - +LiO2 * →Li2O2 * (Formula 5) Here, the "*" represents a neutral Li vacancy on the surface of the lithium peroxide (Li2O2) by-product.
[0040] Various aspects of the subject matter disclosed herein may remove lithium oxide and lithium peroxide generated during operation of the battery 100 from the transport pores 112 and transport pathways 114 during the operating cycle of the battery 100, thereby allowing the transport pores 112 and transport pathways 114 to provide a sufficient amount of oxygen to generate lithium ions and free electrons during the cycling of the battery 100. In some embodiments, the cathode 110 may comprise a network of storage pathways and storage cavities in fluid communication with the network of transport pores 112 and transport pathways 114. In some aspects, the network of storage pathways may remove undesirable by-products from the transport pores 112 and transport pathways 114, and the network of storage cavities may store or otherwise retain undesirable by-products removed from the network of transport pores 112 and transport pathways 114, as described in more detail with reference to FIG. 2. In this manner, lithium oxide and lithium peroxide produced during operation of battery 100 may not accumulate at or near the openings of pores 112 and therefore may not interfere with the supply of oxygen provided from the ambient air 170 to activate and / or operate battery 100.
[0041] FIG. 2 shows a diagram illustrating a cathode 200 according to some embodiments. The cathode 200 may be an example of the cathode 110 of FIG. 1 and may be formed from a scaffolded carbonaceous material 224 (e.g., a plurality of carbonaceous structures 225 and / or a coalesced agglomerate of few-layer graphene other than a group of porous non-hollow carbonaceous spheres (NHCS) particles 226). In some embodiments, the scaffolded carbonaceous material 224 and / or the plurality of carbonaceous structures 225 associated with the cathode 110 may exhibit increased resistance to oxidation during a charging cycle of the battery (compared to a conventional lithium-air battery), which may increase the operating time of the lithium-air battery. In some examples, the graphenized material associated with the carbonaceous structures 225 may be functionalized with polar groups to improve wetting of surfaces within the respective carbonaceous structures 225.
[0042] In some embodiments, the cathode 200 may include a plurality of pores 210a-210b, a plurality of transport channels 220, a plurality of storage channels 221, and a plurality of cavities 230a-230d formed throughout the cathode 200. In some embodiments, the pores 210a-210b may be examples of the pores 112 of FIG. 1, the channels 220 and 221 may be examples of the channels 114 of FIG. 1, and the cavities 230a-230d may be examples of the cavities 116 of FIG. 1. That is, the pores 210a-210b and the channels 220 may be transport pores and channels, respectively, through which oxygen 171 from the ambient air 170 can enter the interior portion of the cathode 200. The pores 210a-210b and the channels 220 may also be used to return oxygen 172 to the ambient air 170. The channels 221 and cavities 230a-230d may be transport channels and transport cavities, respectively, through which undesirable by-products may be removed from the transport holes 210a-210b and the transport channels 220. Although the example of Fig. 2 shows only two transport holes 210a-210b, several transport channels 220 and storage channels 221, and four cavities 230a-230d, in other embodiments, the cathode 200 may include other numbers of transport holes 210a-210b, transport channels 220, storage channels 221, and cavities 230a-230d.
[0043] In some embodiments, the transport holes 210a-210b and the transport path 220 may form a transport network in fluid communication with the storage network formed by the storage path 221 and the storage cavities 230a-230d. For example, during an operation cycle of the battery 100, oxygen 171 supplied from the ambient air 170 may enter the cathode 200 through the transport hole 210a and be distributed throughout the cathode 200 by the transport path 220. Oxygen 172 released from the cathode 200 may return to the ambient air 170 via the transport path 220 and the transport hole 210b. In this manner, the transport hole 210 and the transport path 220 may supply oxygen from the ambient air 170 to the cathode 200 to ensure that a sufficient amount of oxygen is available for the oxidation and reduction processes associated with the operation cycle of the battery 100. The storage path 221 may remove undesirable by-products (e.g., lithium dioxide and lithium superoxide) from the transport hole 210 and the transport path 220. In some examples, the storage pathway 221 may direct these undesirable by-products toward one or more of the storage cavities 230a-230d, which may hold or store these undesirable by-products. In this manner, the storage pathway 221 and the storage cavities 230a-230d may prevent the undesirable by-products from accumulating in the cathode 200 and blocking one or more of the transport holes 210 and / or the transport pathway 220.
[0044] The transport holes 210a-210b, the transport pathways 220, the storage pathways 221, and the storage cavities 230a-230d may be defined in shape, size, and / or orientation by a plurality of carbonaceous structures 225 distributed throughout the cathode 200. In various embodiments, some of the carbonaceous structures 225 may be tailored to exhibit hydrophilic properties, for example, to attract and / or retain water vapor associated with the operation of a lithium-air battery. In some examples, exposed surfaces of a first group or plurality of carbonaceous structures 225 may be tailored to be hydrophilic using a "bottom-up" synthesis procedure, such as self-nucleation from a carbon-containing vapor stream in a reaction vessel. As previously mentioned, each of the carbonaceous structures 225 may be formed by the coalescence of a corresponding group of porous non-hollow carbonaceous spherical (NHCS) particles 226. In some embodiments, the transport holes 210 may have a major dimension (e.g., width or diameter) in the approximate range of 0.6 nanometers (nm) to 6.6 nm to retain reaction by-products, and the transport channels 220 may each have a dimension of about 5.0 to 10.0 microns (or other suitable dimensions that allow oxygen gas provided from the ambient air 170 to enter the cathode 200 and diffuse throughout the cathode 200). The disclosed dimensions may accommodate wetting (e.g., by condensation of vapors onto the respective surfaces) of the exposed surfaces (e.g., 3.0 nm to 5.5 nm, 5.5 nm to 6.0 nm, etc.) of at least some of the carbonaceous structures of the plurality of carbonaceous structures 225. In addition, control of the polarity of the exposed surfaces of at least some of the carbonaceous structures of the respective carbonaceous structures 225 may facilitate and / or reduce evaporation of solvents (e.g., carbonates, ethers, and / or esters, and / or aprotic solvents, etc.). In this manner, the surface interaction between at least a portion of the solvent introduced into the cathode 200 and the exposed surfaces of the carbonaceous structure 225 can be tailored or adjusted.
[0045] The storage channels 221 may each have a diameter of about 0.1 to 5.0 microns (or other suitable dimensions that allow for removal of the lithium oxide by-product from the transport channels 220 and deposition of the lithium oxide by-product in one or more of the cavities 230a-230d). In some embodiments, one or more of the transport channels 220 may be connected to one or more of the storage channels 221 associated with the storage site network. For example, as shown in FIG. 2, each of the storage cavities 230a-230d associated with the storage site network may be connected to the pores 210 and / or the transport channels 220 via corresponding storage channels 221 that permeate the cathode 110. In some embodiments, the discharge capacity of the battery 100 may be based at least in part on the diameter of the storage channels 221 relative to the diameter of the transport channels 220. For example, a transport channel 220 having a relatively large diameter may induce a greater amount of oxygen 171 per unit time than a transport channel 220 having a relatively small diameter.
[0046] Aspects of the present disclosure recognize that some of the undesirable by-products (e.g., lithium oxide) may remain within a certain distance after being generated during operation of the battery, and therefore may not travel a sufficient distance to reach one of the transport paths 220 (or storage paths 221). These undesirable by-products may remain in the outer portion of the cathode 120 and block the openings of the pores 210a-210b. Thus, in some implementations, for example, the width or diameter of the openings of the pores 210a-210b may be increased to reduce the likelihood of blockage by these undesirable by-products, which may increase the discharge rate of a lithium-air battery, such as the battery 100 of FIG. 1.
[0047] In some embodiments, each carbonaceous structure 225 may include a plurality of NHS particles 226, and each NHS particle 226 may include and / or be formed from a stack of 3-15 graphene nanosheets (not shown in FIG. 2). Each graphene nanosheet may have a major dimension of less than 1 μm, and some graphene nanosheets may include mesopores. For example, each mesopore may be about 1 μm in diameter.cc / g (For example, 1.5 cc / g ~2.0 cc / g ) during fabrication. Cathode 200 may form from carbon-containing free radical species that self-nucleate without the need for seed particles to form unique 3D carbonaceous structures including graphene nanosheets doped with nitrogen and / or sulfur. In some embodiments, cathode 200 may be treated with ozone (O3) during fabrication to define carbonaceous structures therein, resulting in a cathode that can be as large as 5m 2 / g ~3,000m 2 / g In addition, the cathode 200 may include one or more surfaces exposed to the ambient air 170 so that a catalyst (e.g., manganese oxide, nickel oxide, cobalt, platinum, gold, etc.) may be deposited on the surface.
[0048] Heteroatom doping of graphene used to generate the NHCS particles 225 of FIG. 2 may improve the overall electroactivity of the cathode 200. For example, nitrogen-doped carbon nanotubes with up to 10.2 atomic percent (at%) nitrogen may be used as a shaped cathode material for the NHCS particles 225 of the cathode 200. In addition, pyridinic nitrogen-rich carbon materials may be used to form the NHCS particles 225 and provide oxygen adsorption. For example, in-plane pyridinic nitrogen may exhibit higher activity in promoting the nucleation of lithium peroxide clusters compared to pristine nitrogen and / or graphitic nitrogen. By doping the carbonaceous material of the cathode with multiple types of heteroatoms, many bifunctional cathode materials such as nitrogen-doped carbon nanotubes (CNTs), nitrogen-doped graphene, sulfur-doped graphene, and nitrogen, sulfur co-doped graphene may be applied to the cathode 200. Nitrogen doping may improve the catalytic activity of the carbonaceous material by manipulating the local electronic structure, thereby providing a higher concentration of electroactive sites per unit volume. Sulfur-doped graphene may also provide cycling stability due to the stability of the -CSC- and -C==S- structures.
[0049] 3D nanoporous undoped, N-doped, and S-doped graphene materials may be used to synthesize NHS particles 222 for the cathode 110 by nanoporous metal-based chemical vapor deposition (CVD) using benzene, pyridine, or thiophene as carbon, nitrogen, and sulfur sources. Alternatively, metal-free graphene may be used to generate NHCS particles 225 for the cathode 200, providing a capacity of 10,400 mAh / g and up to 300 cycles at 1,000 mAh / g. When constructed with such nanoporous graphene, the charge overpotential of the cathode 200 may be relatively high, resulting in relatively low energy efficiency. This issue may be addressed by tailoring the surface chemistry of the nanoporous graphene and / or integrating it with a compatible redox mediator that facilitates charging.
[0050] FIG. 3 shows a diagram 300 of an exemplary polymer network 310, according to some embodiments. In some aspects, the polymer network 310 can be an example of the polymer network 150 of FIG. 1. The polymer network 310 can be non-conductive and disposed on the anode 302. In this manner, the polymer network 310 can avoid additional lithium plating on exposed lithium-containing surfaces (e.g., surfaces elevated relative to the bulk of the anode 302). The anode 302 can be formed as an alkali metal layer having one or more exposed surfaces that include any number of alkali metal-containing nanostructures or microstructures. The alkali metals can include, but are not limited to, lithium, sodium, zinc, indium, and / or gallium. The anode 302 can release alkali ions during the operation cycle of the battery.
[0051] A layer 314 of carbonaceous material may be grafted with fluorinated polymer chains and deposited on one or more exposed surfaces of the anode 302. The grafting may be based on activating the carbonaceous material with one or more radical initiators, such as benzoyl peroxide (BPO) or azobisisobutyronitrile (AIBN), followed by reaction with monomer molecules. The polymer network 310 may be based on the fluorinated polymer chains and the carbonaceous material crosslinked to each other in the layer 314, such that the layer 314 is consumed during the formation of the polymer network 310. In some embodiments, the polymer network 310 may have a thickness of about 0.001 μm to 5 μm and may include about 0.001% to 2% by weight of fluorinated polymer chains. In some other embodiments, the polymer network 310 may comprise between about 5% and 100% by weight of the carbonaceous material grafted with fluorinated polymer chains, and the remainder being a fluorinated polymer, or one or more non-fluorinated polymers, or one or more crosslinking monomers, or combinations thereof. In one embodiment, the carbonaceous material grafted with fluorinated polymer chains may comprise between 5% and 50% by weight of the fluorinated polymer chains and the remainder being a carbonaceous material.
[0052] During cycling of the battery, the carbon-fluorine bonds in the polymer network 310 may chemically react with lithium metal to convert to carbon-lithium bonds (C-Li). These C-Li bonds, in turn, may further react with the carbon-fluorine bonds in the polymer network 310 via the Wurtz reaction 350 to further crosslink the polymer network by forming new carbon-carbon (C-C) bonds and also generate alkali metal-containing fluorides, e.g., lithium fluoride (LiF). The additional polymer network crosslinking resulting in the uniform formation of alkali metal-containing fluorides thereby suppresses alkali metal dendrite formation 340 associated with the anode 302, thereby improving battery performance and life. In one embodiment, grafting of fluorinated m / acrylate (FMA) to one or more exposed graphene surfaces of the carbonaceous material in the layer 314 may be performed in an organic solution resulting in, for example, graphene-grafted-poly-FMA and / or the like. The incorporation of carbon-fluorine bonds into the exposed graphene surface may allow a Wurtz reaction 350 to occur between the carbon-fluorine bonds and the metal surface of an alkali metal (e.g., lithium) provided by the anode 302. Completion of the Wurtz reaction 350 may thus result in the formation of a polymer network 330. In some embodiments, the polymer network 330 may include a density gradient 316 following completion of the Wurtz reaction 350. The density gradient 316 may include interconnected graphene flakes and may be infused with one or more metal fluoride salts formed in situ. Additionally, the porosity and / or mechanical properties of the layer may be tailored by the combination of carbon loading and / or functionalized carbon, each with a unique and / or distinct physical structure.
[0053] In some implementations, the carbonaceous material in the density gradient 316 may include one or more of flat graphene, wrinkled graphene, carbon nanotubes (CNTs), or carbon nano-onions (CNOs) in the form of spherical solid structures (e.g., as illustrated in Figures 4A and 4B). In one implementation, the graphene nanoplatelets may be dispersed throughout and separated from one another within the polymer network 310. The dispersion of graphene nanoplatelets may include one or more different concentration levels. In one implementation, the dispersion of graphene nanoplatelets may include at least a portion of the carbonaceous material functionalized with at least a portion of the fluorinated polymer chains.
[0054] For example, the fluorinated polymer chain may include one or more acrylate or methacrylate monomers, including vinyl-based monomers including 2,2,3,3,4,4,5,5,6,6,7,7-dodecafluoroheptyl acrylate (DFHA), 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecyl methacrylate (HDFDMA), 2,2,3,3,4,4,5,5-octafluoropentyl methacrylate (OFPMA), tetrafluoropropyl methacrylate (TFPM), 3-[3,3,3-trifluoro-2-hydroxy-2-(trifluoromethyl)propyl]bicyclo[2.2.1]hept-2-yl methacrylate (HFA monomer), or 2,3,4,5,6-pentafluorostyrene (PFSt).
[0055] In some embodiments, fluorinated polymer chains are grafted onto the surface of the carbonaceous material layer, which may chemically interact with one or more surfaces of the alkali metal of the anode via the Wurtz reaction 350. In organic chemistry, organometallic chemistry, and inorganic backbone polymers, the Wurtz reaction is a coupling reaction whereby two alkyl halides react with sodium metal (or some other metal) in a dry ether solution to form a higher alkane. In this reaction, an alkyl halide is treated with an alkali metal, e.g., sodium metal, in a dry ether (water-free) solution to produce a higher alkane. In the case of the lithium intermediate of the Wurtz reaction, a highly polar and reactive carbon-lithium metal bond is produced, which chemically reacts with a carbon halide (e.g., fluoride) bond to give a newly formed C-C bond and lithium fluoride. The formation of the new C-C bond allows the Wurtz reaction to be used, for example, to produce higher alkanes containing an even number of carbon atoms. C-F+2Li → C-Li + +LiF (Equation 4) C-Li + +CF→C-C+LiF (Formula 5)
[0056] Other metals have also been used to affect the Wurtz bond, particularly mixtures of silver, zinc, iron, activated copper, indium, and manganese with copper chloride. A related reaction involving aryl halides is called the Wurtz-Fittig reaction. This can be explained by the formation of a free radical intermediate and subsequent disproportionation to produce an alkene. The Wurtz reaction 350 occurs via a free radical mechanism that allows for a side reaction to produce an alkene by-product. In some embodiments, the chemical interaction associated with the above Wurtz reaction can form an alkali metal fluoride, such as lithium fluoride.
[0057] In one embodiment, the polymer network 310 can include an interfacial layer 318 in contact with the anode 302. The protective layer 320 can be disposed on the interfacial layer 318, which can be based on a Wurtz reaction 350 at the interface between the anode 302 and the polymer network 310. The interfacial layer 318 can have a relatively high crosslink density (e.g., of a fluorinated polymer and / or the like), a high metal fluoride concentration, and a relatively low carbon-fluorine bond concentration. In contrast to the interfacial layer 318, the protective layer 320 can have a relatively low crosslink density, a low metal fluoride concentration, and a high carbon-fluorine bond concentration.
[0058] In some embodiments, the interfacial layer 318 may include crosslinkable monomers, such as methacrylate (MA), acrylate, vinyl functional groups, or a combination of epoxy and amine functional groups. In one embodiment, the protective layer 320 may be characterized by a density gradient 316. As such, the density gradient 316 may be related to one or more self-healing properties of the protective layer 320 and / or may reinforce the polymer network 310. In some embodiments, the reinforced protective layer 320 may further inhibit alkali metal dendrite formation 340 from the anode 302 during battery cycling.
[0059] In operation, the interfacial layer 318 may inhibit alkali metal dendrite formation 340 associated with the anode 302 by uniformly generating metal fluorides, e.g., lithium fluoride, at the interface along the length of the anode 302. The uniform generation of metal fluorides may ultimately inhibit alkali metal dendrite formation 340 by causing dissolution of the dendrite surface, e.g., by conversion to metal fluoride. Additionally, bridging of the fluorinated polymer chains on the remaining dendrites may further inhibit alkali metal dendrite formation 340. In some embodiments, the density gradient 316 may be adjusted to control the degree of bridging between the fluorinated polymer chains.
[0060] FIG. 4A shows a micrograph 400 of a plurality of carbonaceous spherical particles 402 according to some embodiments. In some examples, the carbonaceous spherical particles 402 may be examples of the NHCS particles 226 of FIG. 2. Each of the carbonaceous spherical particles 402 may include a solid core region having a relatively low carbon density surrounded by various monolithic carbon growths and / or layerings having a relatively high carbon density. The carbonaceous spherical particles 402 may include multiple concentric multi-layered fullerenes and / or similarly shaped carbonaceous structures organized at various levels of density and / or concentration. For example, the final shape, size, and graphene configuration of each carbonaceous spherical particle 402 may depend on various manufacturing processes. In some embodiments, the carbonaceous spherical particles 402 may exhibit poor water solubility. Therefore, in some embodiments, non-covalent functionalization may be utilized to alter one or more dispersibility properties of the carbonaceous spherical particles 402 without affecting the inherent properties of the underlying carbon nanomaterial. In some embodiments, the underlying carbon nanomaterial may be a mixture of sp 2 The carbonaceous spherical particles 402 may be capable of forming carbon nanomaterials. In some embodiments, each of the carbonaceous spherical particles 402 may have a diameter of about 20-500 nm. In various embodiments, groups of the carbonaceous spherical particles 402 may coalesce and / or aggregate to form carbonaceous structures 404. In some examples, the carbonaceous structures 404 may be examples of the carbonaceous structures 225 of FIG. 2). Additionally, groups of the carbonaceous structures 404 may coalesce and / or combine to form agglomerates 406.
[0061] FIG. 4B shows a micrograph 450 of a carbonaceous structure 460, according to some embodiments. In some examples, the carbonaceous structure 460 can be an example of the carbonaceous structure 404 of FIG. 4A. In one embodiment, the outer carbonaceous shell-type structures 442, 444, and 446 can fuse together to form the carbonaceous structure 460. A group of the carbonaceous structures 460 can coalesce and / or combine to form the agglomerate 406 of FIG. 4A. In some aspects, the core region 448 of each carbonaceous shell-type structure 446 can be tunable, for example, in that the core region 448 can include various defined concentration levels of interconnected graphene structures. In some embodiments, each carbonaceous shell-type structure 446 can have a first concentration of interconnected carbon at or near each carbonaceous shell-type structure 446 of between about 0.1 g / cc and 2.3 g / cc. Each carbonaceous shell-type structure can have pores for transporting lithium ions extending inwardly toward the core region 448.
[0062] In some embodiments, the pores of each of the carbonaceous shell-type structures 442, 444, and 446 may have a width or dimension of about 0.0 nm to 0.5 nm, about 0.0 to 0.1 nm, about 0.0 to 6.0 nm, or about 0.0 to 35 nm. Each of the carbonaceous shell-type structures 442, 444, and 446 may also have a second concentration at or near the core region 448 that is different from the first concentration. For example, the second concentration may include a plurality of relatively low density carbonaceous regions arranged in a concentric ring. In one embodiment, the second concentration may be lower than the first concentration, at about 0.0 g / cc to 1.0 g / cc or about 1.0 g / cc to 1.5 g / cc. In some embodiments, the relationship between the first concentration and the second concentration may be utilized to maximize lithium ion transport and gaseous oxygen uptake while providing suitable retention locations for lithium oxide.
[0063] In some embodiments, at least a portion of the carbonaceous shell-type structures 442, 444, and 446 may comprise carbon nano-onion (CNO) oxides organized as monolithic and / or interconnected growths and produced in a thermal reactor. In one embodiment, the carbonaceous shell-type structures 442, 444, and 446 may be decorated with cobalt nanoparticles according to the following example recipe: Cobalt (II) acetate (C4H6CoO4), a cobalt salt of acetate (often found as tetrahydrate Co(CH3CO2)24H2O, sometimes abbreviated as Co(OAc)2·4H2O), is flowed into a thermal reactor in a ratio of about 59.60% by weight, which corresponds to 40.40% by weight of carbon (referring to carbon in the CNO form), so that the active sites of the CNO oxides may be functionalized with cobalt. In some embodiments, a suitable gas mixture used to produce cobalt-decorated CNO may include the following steps: · Ar purge for 30 minutes at 0.75 standard cubic feet per minute (scfm); ·Ar purge changed to 0.25scfm for run; A temperature increase from 25°C to 300°C in 20 minutes; and · Temperature increase from 300°C to 500°C in 15 minutes; may be included.
[0064] The carbonaceous material described with reference to Figures 4A and 4B may include or be otherwise formed from one or more instances of graphene, which may include a monolayer of carbon atoms with each atom bonded to three adjacent atoms in a honeycomb structure. The monolayer may be a discrete material constrained in one dimension, such as within or at the surface of a condensed phase. For example, graphene may grow outward only in the x and y planes (but not in the z plane). Thus, graphene may be a two-dimensional (2D) material that includes one or more layers with atoms in each layer strongly bonded (such as by multiple carbon-carbon bonds) to adjacent atoms in the same layer.
[0065] In some implementations, the graphene nanoplatelets (e.g., the forming structures included in each of the carbonaceous shell-type structures 442, 444, and 446) may include multiple instances of graphene, such as a first graphene layer, a second graphene layer, and a third graphene layer, all stacked vertically on top of each other to form a decorative and unique 3D carbonaceous structure. Each of the graphene nanoplatelets, which may be referred to as GNPs, may have a thickness of 1 nm to 3 nm and lateral dimensions in the range of about 100 nm to 100 μm. In some implementations, the graphene nanoplatelets may be produced by roll-to-roll (R2R) production, by multiple plasma spray torches arranged in series. In some embodiments, the R2R production may include deposition on successive substrates that are processed as rolled sheets, including transfer of the 2D material(s) to separate substrates. The plasma spray torch used in the R2R process can spray the carbonaceous material at different concentration levels to produce specific concentration levels of graphene nanoplatelets, thereby providing a fine level of tunability to the cathode 110 of FIG. 1 and / or the cathode 200 of FIG. 2.
[0066] 5A shows an SEM micrograph 500A of graphene powder, according to some embodiments. The adjacent graphenized sheets and / or layers in the micrograph 500A have a complex 3D structure to prevent graphene restacking, which may avoid some of the drawbacks of using 2D graphene.
[0067] FIG. 5B shows an SEM micrograph 500B of nodular carbon produced by a thermal process, according to some embodiments. The nodular carbon shown in micrograph 500B can be used to produce NHS particles 222 in the cathode 110 of FIG. 1 and / or FIG. 2. In this manner, the nodular carbon of micrograph 500B can produce a unique dual pore system that can simultaneously retain lithium oxide while facilitating the free passage of gaseous oxygen to the interior region of the cathode 110, if needed, for optimal lithium-air battery operation. The nodular carbon shown in micrograph 500B can be characterized by pores, each pore having a diameter between approximately 0.6 nanometers (nm) and 6.6 nm, thereby allowing the retention of lithium oxide within these pores.
[0068] 5C shows an SEM micrograph 500C of carbon dioxide (CO2) treated carbon, according to some embodiments. The 3D graphenized and / or carbonaceous material shown in micrograph 500C can be produced by CO2 treatment and used to generate the cathode 110 of FIG. 1 and / or the NHS particles 222 of FIG. 2 of the battery 100 of FIG. 1.
[0069] 5D shows an SEM micrograph 500D of carbon dioxide (CO2) treated carbon, according to some embodiments. The 3D graphenized and / or carbonaceous material shown in micrograph 500C can be produced by CO2 treatment and used to generate the cathode 110 of FIG. 1 and / or the NHCS particles 226 of FIG. 2 of the battery 100 of FIG. 1.
[0070] 6 shows a micrograph 600 of three-dimensional (3D) graphene after carbon dioxide (CO2) treatment, according to some embodiments. In some examples, the treated 3D graphene can be used to produce NHCS particles 226 in the cathode 110 of the lithium-air batteries 100 and 200 of FIGS. 1 and 2, respectively.
[0071] 7 shows a graph 700 illustrating an example distribution of pore volume versus pore width for pores in graphenized nanosheets of NHCS particles 226 of cathode 110 of FIG. 2 or other carbonaceous materials described herein, according to some embodiments. As shown in graph 700, pores associated with relatively high pore volumes may have relatively low pore widths, such that, for example, pore widths generally increase as pore volume decreases. In some embodiments, pores having a pore width less than about 1.0 nm may be referred to as micropores, pores having a pore width between about 3 and 11 nm may be referred to as mesopores, and pores having a pore width greater than about 24 nm may be referred to as macropores.
[0072] Referring also to FIG. 1 , the lithium-air battery 100 may be activated by allowing oxygen supplied from the ambient air 170 to enter the interior portion of the lithium-air battery 100 through various pores 112 and pathways 114 formed in the cathode 110. As previously mentioned, the oxygen supplied to the lithium-air battery 100 reacts with the lithium supplied by the anode 120 to produce lithium ions and free electrons at or near the anode 120. The lithium ions migrate from the anode 120 to the cathode 110 through the electrolyte 130 and react with oxygen at or near the cathode 110 to produce lithium oxide. The free electrons can migrate from the anode 120 to the cathode 110 through an external circuit, thereby generating an electric current through the external circuit. During a battery charging cycle, the oxygen supplied from the ambient air 170 donates electrons to the lithium oxide present at or near the cathode 110 to produce lithium ions and electrons. The electrochemical potential between the anode 120 and the cathode 110 may cause the lithium ions to return to the anode 120 where they may accumulate and plate lithium onto the anode 120 .
[0073] As described with reference to FIG. 2, lithium oxide (and other undesirable by-products) produced during operation of the battery 100 may block the openings of the pores 210a-210b that are responsible for delivering oxygen from the ambient air 170 to the interior portions of the battery 100. In some implementations, the width or diameter of the openings of the pores 210a-210b may be increased to reduce the likelihood of blockage by lithium oxide (and other undesirable by-products). However, aspects of the present disclosure also recognize that increasing the width or diameter of the pore openings may unintentionally allow water droplets and / or water vapor to enter the cathode 110 through the pores 112 and channels 114 described with reference to FIG. Furthermore, while the hydrophilicity of at least some of the carbonaceous structures 225 that define the transport pores 210 and transport pathways 220 in the cathode 110 allows these carbonaceous structures 225 to attract or retain water vapor associated with various chemical reactions in the battery 100, the hydrophilicity of these carbonaceous structures 225 may allow water droplets to accumulate on the surfaces of these carbonaceous structures 225. In some instances, the accumulated water droplets may enter the pore pathways 114 formed in the cathode 110, diffuse through at least some portions of the cathode 110, and react in an undesirable manner with lithium in the battery. This phenomenon, commonly referred to as "flooding," not only reduces the specific capacity of the battery 100, but may also shorten the life of the battery.
[0074] FIG. 8A shows an example 800 illustrating a water droplet formed or disposed on an outer surface of a few-layer graphene (FLG) 810. The FLG 810 may include 3-15 layers of carbon atoms and may be used to form a carbonaceous structure 225 that defines the various pores 210 and pathways 220 formed in the cathode 110 of the battery 100 of FIG. 1. Specifically, a plurality of example FLGs 810 (and / or porous non-hollow carbonaceous spherical (NHCS) particles 226 described with reference to FIG. 2) may coalesce with one another to form an agglomerate of carbonaceous material that defines the shape, size, and / or orientation of the pores 210 and pathways 220 formed throughout the cathode 110. A first pore 811 having a first diameter (d1) is formed in a top surface 801 of the FLG 810 and may be in fluid communication with one or more of the pathways and / or cavities (not shown for simplicity) formed throughout the FLG 810. A second pore 812 having a second diameter (d2) is formed in the lower surface 802 of the FLG 810 and may be in fluid communication with one or more of the passages and / or cavities (not shown for simplicity) formed throughout the FLG 810. The first pore and the second pores 811 and 812 may be separated by a pore spacing distance. In some aspects, the first diameter d1 is greater than the second diameter d2, for example, such that the opening of the first pore 811 is wider than the opening of the second pore 812.
[0075] In the example of FIG. 8A, a first water droplet 821 is formed or disposed on the top surface 801 of the FLG 810, and a plurality of second water droplets 822 are formed or disposed on the bottom surface 802 of the FLG 810. For purposes of illustrating the tunability of the FLG 810 only, the top portion of the FLG 810 may be tuned to exhibit hydrophobic properties, and the bottom portion of the FLG 810 may be tuned to exhibit hydrophilic properties. The hydrophobic properties of the top portion of the FLG 810 may prevent the water droplet 821 from moving along the top surface 801 of the FLG 810 and entering the first pore 811. Meanwhile, the hydrophilic properties of the bottom portion of the FLG 810 may enable the plurality of water droplets 802 to form a continuous water film along the bottom surface 802 of the FLG 810. In some examples, the continuous film of water droplets 822 may be in equilibrium due to cohesive forces within the water film and adhesive forces between the water droplets and the FLG surface. As shown, the surface tension of the continuous film of the water droplet 822 may prevent the water droplet 822 from entering the second pore 812, due at least in part to the relatively small diameter d2 of the second pore 812 (e.g., compared to the relatively large diameter d1 of the first pore 811).
[0076] FIG. 8B shows an example 850 illustrating an example flooding (not shown for simplicity) of a lithium-air battery including a cathode formed at least in part by the FLG 810 described with reference to FIG. 8A. As discussed with reference to FIG. 8A, the first pores 811 have a relatively large pore opening (indicated by a first diameter d1) and the second pores 812 have a relatively small pore opening (indicated by a second diameter d2, where d1>d2). In some examples, the relatively large opening of the first pores 811 may allow water droplets 821 collected on the top surface 801 of the FLG 810 to penetrate the interior portions of the first pores 811, flooding them. Similarly, the larger diameter d2 of the second pores 812 in the example of FIG. 8B may allow some of the water droplets 822 in the continuous film to penetrate the interior portions of the second pores 812, flooding them.
[0077] In some embodiments, the FLGs 810 (and other carbon-based structures) that define the various pores 210 and pathways 220 throughout the cathode 110 can be tailored in a manner that allows lithium to be deposited within pores and / or cavities formed in the FLGs 801 that are not susceptible to flooding. Specifically, in some examples, the FLGs 810 can be tailored such that the respective diameters of the first pores 811 (d1) and second pores 812 (d2) are both small enough to prevent flooding of the respective first and second pores 811 and 812.
[0078] FIG. 9A shows an example 900 illustrating the state of charge of a lithium-air battery. In some embodiments, the FLGs 810 can be used to form at least a portion of the cathode of a lithium-air battery. More specifically, the FLGs 810 can be the building blocks for the carbonaceous structure that defines the various pores 210 and pathways 220 in the cathode 110 of the battery 100 of FIG. 1. As previously mentioned, the FLGs 810 (and / or other carbonaceous materials such as the porous NHCS particles 226 or CNO particles of FIG. 2, among other examples) can coalesce with one another to form aggregates of carbonaceous material that define the shape, size, and / or orientation of the pores 210 and pathways 220 throughout the cathode 110.
[0079] The FLG810 is made up of pores 910 containing some Li2O crystals 912 and hexagonal LiO x 9 includes a crystal 914 and three droplets 921-923 collected on the top surface 801 of the FLG 810. Each of the three droplets 921-923 is disposed at a corresponding first angle (θ1) relative to the top surface 801 of the FLG 810. The middle droplet 922 is positioned above a pore 910 at a second angle (θ2) relative to the top surface 801 of the FLG 810, the pore 910 having a diameter (d2). In various embodiments, the diameter d2 of the pore 910 may be small enough to prevent water from passing into or accumulating within the pore 910.
[0080] Hexagonal LiO x Crystal 914 is hexagonal LiOx The crystal 914 is positioned a first distance (L1) away from the wall of the pore 910 so that the crystal 914 does not contact the carbon material within the pore 910. In some examples, the first distance (L1) is the electron tunneling distance (which allows the electrons (e - ) is smaller than the angle θ2 that allows tunneling through FLG 810 into pore 910. The resulting transfer of electrons to pore 910 allows the electrons to react with Li2O912 to convert Li2O912 to lithium metal, thereby providing the active material for the operation of an associated lithium-air battery. In this manner, stoichiometric Li2O crystals (such as Li2O crystals 912) in electrochemical communication with the graphene can react with the electrons to form lithium metal. In some embodiments, when angle θ2 is greater than 90 degrees, pore 910 may be considered hydrophilic, and when angle θ2 is less than 90 degrees, pore 910 may be considered hydrophobic.
[0081] 9B shows an example 950 illustrating a discharged state of a lithium-air battery. In some embodiments, the FLG 810 can be used to form at least a portion of a cathode of a lithium-air battery. More specifically, the FLG 810 can be used to form a carbonaceous structure that defines the various pores 210 and pathways 220 formed in the cathode 110 of the battery 100 of FIG. 1. As described, the FLG 810 and / or the various porous non-hollow carbonaceous spherical (NHCS) particles 226 described with reference to FIG. 2 can coalesce with one another to form an aggregate of carbonaceous material that defines the shape, size, and / or orientation of the pores 210 and pathways 220 throughout the cathode 110.
[0082] FLG810 is Li2O crystal 912, hexagonal LiO x In the example of FIG. 9B, the hexagonal LiO x Crystal 914 is the hexagonal LiO x9B. Specifically, the hexagonal LiO x The arrangement of the crystal 914 makes the distance L2 larger than the electron tunneling distance, and the electrons tunnel through the FLG 810 into the pore 910, forming a hexagonal LiO x This can prevent the non-stoichiometric LiO from reacting with the crystal 914. x Crystal (LiO x The LiO crystals (e.g., 914) may, for example, be formed by electrons tunneling through the pores 910 to form non-stoichiometric LiO x Since it cannot react with the crystal, it is not converted to lithium metal. In some embodiments, if the angle θ2 is greater than 90 degrees, the pore 910 may be considered hydrophilic, and if the angle θ2 is less than 90 degrees, the pore 910 may be considered hydrophobic.
[0083] FIG. 10 shows an example 1000 illustrating various types of FLGs. Specifically, the example 1000 shows an FLG model 1010 as a flat sheet and a curved FLG 1020 as an arched surface. The example 1000 also shows multi-layered fullerenes 1030 as spherical CNO particles with internal pores that are not exposed to ambient air, which may prevent the multi-layered fullerenes 1030 from reacting with oxygen (or water) provided by ambient air. The example 1000 also shows processed CNO particles 1040 with tailored or configured pore openings 1042 through which ambient air may enter and diffuse across the cathode formed by the processed CNO particles 1040.
[0084] FIG. 11 illustrates a carbonaceous aggregate 1100 according to some embodiments. The carbonaceous aggregate 1100 includes a plurality of CNO particles 1110 and 1120 (only two CNO particles 1110-1120 are shown for simplicity). In some examples, the carbonaceous aggregate 1100 may be an example of the carbonaceous structure 225 described with reference to FIG. 2. Each of the CNO particles 1110 and 1120 may be treated and tuned to achieve a desired width of the openings 1111 and 1121 of the CNO particles 1110 and 1120, respectively. As shown, oxygen (O2) provided by the ambient air may pass through the walls of the carbonaceous aggregate 1100 into the interior portion of the carbonaceous aggregate 1100. In some embodiments, the plurality of CNO particles 1110 and 1120 can be tailored to exhibit hydrophobic properties that can repel water vapor or water droplets (H20), such as water droplets, from entering the interior portion of the carbonaceous aggregate 1100. In some embodiments, the hydrophobically tailored CNO particles 1110 and 1120 can retain water within various transport pathways between the CNO particles 1110-1120 (not shown for simplicity). In this manner, tailoring the CNO particles 1110 and 1120 to exhibit hydrophobic properties can prevent water from entering the battery through the pore openings and reacting (undesirably) with lithium.
[0085] In some examples, each of the CNO particles 1110 and 1120 may have a radius of about 5 nm to 25 nm. In other examples, the radius of the CNO particles 1110 and 1120 may be about 5 nm to 50 nm. In some other examples, the radius of the CNO particles 1110 and 1120 may be between about 3 nm to 500 nm. Aspects of the subject matter disclosed herein recognize that when the radius of each CNO particle is less than about 100 nm, a single cavity may be formed during the formation of each CNO particle. The formation and adjustment of a single cavity within the CNO particles 1110 and 1120 may have the advantage of being relatively easy to manage (compared to the formation and adjustment of multiple cavities). On the other hand, when the radius of each CNO particle reaches or exceeds about 100 nm, multiple cavities may be formed during the formation of each CNO particle. Multiple cavities in a CNO particle may allow the pathways formed in the CNO particle (e.g., pathway 220 described with respect to FIG. 2) to be more tortuous than pathways formed in a CNO particle having a single cavity. In addition, providing multiple cavities in a CNO particle may increase the amount of lithium that can be stored in the cavities of the CNO particle, thereby increasing the specific capacity of an associated lithium-air battery.
[0086] For example, as shown in Figure 11, the first CNO particle 1110 has a radius R1 of less than about 100 nm, and the second CNO particle 1120 has a radius R2 of more than about 100 nm. Thus, the first CNO particle 1110 may include a single cavity (not shown for simplicity) associated with a relatively less tortuous path 1113 between the opening 1111 and the core 1112 of the first CNO particle 1110, and the second CNO particle 1120 may include multiple cavities (not shown for simplicity) associated with a relatively more tortuous path 1123 between the opening 1121 and the core 1122 of the second CNO particle 1120. The relatively less tortuous path 1113 formed in the first CNO particle 1110 allows oxygen supplied by the ambient air to propagate through the CNO particle 1110 toward the core 1112. However, the relatively less tortuous path 1113 also allows water (such as water droplets or water vapor) to penetrate into the interior portion of the first CNO particle 1110, which can lead to flooding of an associated lithium-air battery (such as the lithium-air battery 100 of FIG. 1), as discussed above.
[0087] Conversely, the relatively tortuous pathways 1123 formed in the second CNO particle 1120 may prevent water droplets from entering the interior portion of the second CNO particle 1120 (e.g., due to the increased travel distance between the pore openings 1121 and the core 1122 through the relatively tortuous pathways 1123), thereby preventing flooding of the associated lithium-air battery. However, the relatively tortuous pathways 1123 may also limit or inhibit oxygen supplied by the ambient air from flowing through the second CNO particle 1120 and diffusing across the corresponding anode, which, as discussed above, may reduce the specific capacity of the associated lithium-air battery.
[0088] Aspects of the subject matter disclosed herein recognize that optimal performance of a lithium-air battery may involve achieving a desired balance between allowing sufficient amounts of oxygen to propagate into the CNO particles that form the cathode of the lithium-air battery and preventing (or at least inhibiting) water from propagating into such CNO particles. In some embodiments, this desired balance may be achieved by selectively tailoring the carbonaceous materials (such as CNO particles 1110 and 1120 in FIG. 11 ) in the cathode of the lithium-air battery to exhibit a certain level of hydrophilic behavior or to exhibit a certain level of hydrophobic behavior. In some examples, these carbonaceous materials may be tailored to allow lithium to react in various cavities of the CNO particles that are less susceptible to flooding.
[0089] Specifically, in various embodiments, the CNO particles 1110 and 1120 (and other carbonaceous materials or structures) may be etched to configure their respective pore openings 1111 and 1121 to have widths or diameters less than a critical dimension associated with preventing water droplets from entering the respective passages 1113 and 1123. In some examples, as described with reference to FIG. 8A, the exposed surfaces of at least some of the CNO particles in the cathode may be tailored to exhibit hydrophobic properties that may inhibit water droplets from migrating along the surface of the cathode or toward the openings of nearby pores. Additionally or alternatively, as described with reference to FIG. 8A, the exposed surfaces of some other CNO particles in the cathode may be tailored to exhibit hydrophilic properties that cause aligned water droplets to form a continuous water film with sufficient surface tension to prevent the pore openings from flooding the lithium-air battery. In some examples, a plurality of CNO particles (and / or other carbonaceous materials or structures) forming the cathode may be selectively etched to form tortuous transport paths (such as tortuous paths 1123 formed in CNO particles 1120) that allow oxygen supplied by ambient air to diffuse into and throughout the cathode while simultaneously inhibiting water droplets from propagating within or across the cathode.
[0090] As previously mentioned, CNO particles (such as CNO particles 1110 and 1120) or porous non-hollow carbonaceous spherical particles can coalesce with one another to form larger carbonaceous structures that define various pores, pathways, and cavities within the cathode of a lithium-air battery. In various embodiments, the size and porosity of these relatively large carbonaceous structures can be controlled and / or tailored to ensure a certain level of tortuosity of the pathways and / or ensure that their respective pore openings are smaller than a critical dimension. In this manner, the hierarchical pore structure, configured porosity, and tailored behavior of the CNO particles 1110 and 1120 (and / or other carbonaceous materials) used in the cathode of a lithium-air battery can prevent water from entering the pore openings and flooding the lithium-air battery, while at the same time allowing a sufficient amount of oxygen provided by the ambient air to propagate through the various pores and pathways of the cathode and participate in the chemical reactions associated with the generation of the output current (or voltage) of the lithium-air battery. Additionally, by increasing the extent to which a lithium-air battery can prevent water droplets from penetrating and spreading throughout the cathode, embodiments of the subject matter disclosed herein may extend the shelf life of a lithium-air battery, for example, by preventing inadvertent activation of the lithium-air battery caused by exposure of the lithium-air battery to rain, sprinklers, or other sources of water droplets.
[0091] As used herein, a reference to "at least one" or "one or more" of a list of items refers to any combination of those items, including single members. "At least one of a, b, or c" is intended to cover the possibilities of a only, b only, c only, a combination of a and b, a combination of a and c, a combination of b and c, and a combination of a, b, and c.
[0092] The various illustrative components, logic circuits, logic blocks, modules, circuits, operations, and algorithmic processes described in connection with the embodiments disclosed herein, including the structures disclosed herein and structural equivalents thereof, may be implemented as electronic hardware, firmware, software, or a combination of hardware, firmware, or software. The compatibility of hardware, firmware, and software is generally described in terms of the functionality and illustrated in the various illustrative components, blocks, modules, and processes described above. Whether such functionality is implemented in hardware, firmware, or software depends on the application and design constraints imposed on the overall system.
[0093] Various modifications to the embodiments described in this disclosure may be readily apparent to those skilled in the art, and the general principles defined herein may be applied to other embodiments without departing from the spirit or scope of the disclosure. Thus, the claims are not intended to be limited to the embodiments shown herein, but are to be accorded the widest scope consistent with this disclosure, the principles and novel features disclosed herein.
[0094] Moreover, various features described herein in the context of separate embodiments can also be implemented in combination in a single embodiment. Moreover, various features described in the context of a single embodiment can also be implemented in multiple embodiments separately or in any suitable subcombination. Thus, although features may be described above in combination with one another and may even be initially claimed as such, one or more features from a claimed combination may, in some cases, be carved out of the combination, and the claimed combination may be directed to a subcombination or variation of the subcombination.
[0095] Similarly, while operations are shown in the figures in a particular order, this should not be understood as requiring such operations to be performed in the particular order or sequential order shown, or that all of the operations shown be performed, in order to achieve a desired result. Additionally, the figures may generally depict another exemplary process in the form of a flow chart or flow diagram. However, other operations not shown may be incorporated into the exemplary process generally described. For example, one or more additional operations may be performed before, after, simultaneously with, or between the operations shown in the figures. In some circumstances, multitasking and parallel processing may be advantageous. Additionally, the separation of various system components in the embodiments described above should not be understood as requiring such separation in all embodiments, and it should be understood that the program components and systems described may generally be integrated together in a single product or may be included in multiple products.
Claims
1. A lithium-air battery, An anode; a cathode formed of an array of carbonaceous structures and disposed opposite the anode, the cathode comprising: a plurality of pores defined by a first group of carbonaceous structures, the pores configured to allow oxygen supplied from ambient air to enter the cathode; a plurality of interconnected pathways defined by a second group of the carbonaceous structures, the interconnected pathways configured to diffuse the oxygen throughout the cathode; and one or more cavities formed within or associated with each of said pathways, each cavity configured to store lithium metal; and the cathode comprising: an electrolyte dispersed throughout the cathode, the electrolyte being in fluid contact with the anode; one or more openings configured to selectively expose at least a portion of the plurality of pores to the ambient air; The lithium-air battery.
2. 2. The lithium-air battery of claim 1, wherein the anode is composed of lithium metal.
3. 2. The lithium-air battery of claim 1, wherein each carbonaceous structure is based on the coalescence of a corresponding group of carbon nano-onion (CNO) particles.
4. 4. The lithium-air battery of claim 3, wherein each carbonaceous structure further comprises a plurality of interconnected graphene flakes.
5. 4. The lithium-air battery of claim 3, wherein each carbonaceous structure further comprises one or more of flat graphene, wrinkled graphene, curved graphene, or porous non-hollow spherical particles.
6. 4. The lithium-air battery of claim 3, wherein the CNO particles have a radius between about 5 nanometers and 500 nanometers.
7. 4. The lithium-air battery of claim 3, wherein at least a portion of the CNO particles of the first group of carbonaceous structures have a radius greater than 100 nanometers.
8. 8. The lithium-air battery of claim 7, wherein each of said at least some of said CNO particles comprises a plurality of said cavities.
9. 4. The lithium-air battery of claim 3, wherein at least a portion of the CNO particles of the first group of carbonaceous structures are configured to be hydrophobic.
10. 10. The lithium-air battery of claim 9, wherein the hydrophobic CNO particles of the first group of carbonaceous structures inhibit migration of water droplets along a surface toward one or more of the plurality of pores.
11. 4. The lithium-air battery of claim 3, wherein at least a portion of the CNO particles of the second group of carbonaceous structures are configured to be hydrophilic.
12. 12. The lithium-air battery of claim 11, wherein the hydrophilic CNO particles of the second group of carbonaceous structures allow water droplets to form a continuous water film along a surface of each of the hydrophilic CNO particles.
13. 13. The lithium-air battery of claim 12, wherein the continuous water film is in equilibrium due to cohesive forces within the continuous water film and adhesive forces between the continuous water film and the respective surfaces of the hydrophilic CNO particles.
14. 13. The lithium-air battery of claim 12, wherein surface tension associated with the continuous water film prevents the water droplets of the continuous water film from accumulating on the cathode.
15. 2. The lithium-air battery of claim 1, wherein at least a portion of the cavity has a diameter between about 0.6 nanometers and 6.6 nanometers.
16. 2. The lithium-air battery of claim 1, further comprising a plurality of other interconnected pathways defined by a third group of the carbonaceous structures, the plurality of other interconnected pathways configured to remove undesired by-products from at least a portion of the interconnected pathways defined by the second group of the carbonaceous structures.
17. 10. The lithium-air battery of claim 1, further comprising a separator disposed between the anode and the cathode.
18. a protective layer disposed on the anode, the protective layer comprising: a polymer network deposited on one or more exposed surfaces of the anode, the polymer network comprising the carbonaceous structure grafted with a plurality of fluorinated polymer chains crosslinked to each other; a lithium fluoride (LiF) film formed from the polymer network and lithium provided by the anode; 2. The lithium-air battery of claim 1 , comprising:
19. 20. The lithium-air battery of claim 18, further comprising an outer layer deposited on the lithium fluoride film, the outer layer comprising one or more of a polymer or an epoxy encapsulated ionic conductor.
20. 2. The lithium-air battery of claim 1, wherein each of the carbonaceous structures comprises a three-dimensional (3D) stack of graphene nanosheets.